An Examination of the Prevalence, Consumer Profiles, and Patterns of Energy Drink Use, With and Without Alcohol, in Australia. (8th June 2015) - Pennay, Amy; Cheetham, Alison; Droste, Nic; Miller, Peter; Lloyd, Belinda; Pennay, Darren; Dowling, Nicki; Jackson, Alun; Lubman, Dan I.
<x xml:space="preserve">Abstract</x> Background There has been a significant growth in the energy drink (ED) market in Australia and around the world; however, most research investigating the popularity of ED and alcohol and energy drink (AED) use has focused on specific subpopulations such as university students. The aim of this study was to estimate the prevalence, consumption patterns, and sociodemographic correlates of ED and combined AED use among a representative Australian population sample. Methods A computer‐assisted telephone interview survey (n = 2, 000) was undertaken in March–April 2013 of persons aged 18 years and over. Half of the interviews were obtained through randomly generated landline telephone numbers and half through mobile phones. Approximately half of the sample was female (55.5%; n = 1, 110) and the mean age of participants was 45.9 (range 18 to 95, SD 20.0). Results Less than 1 in 6 Australians reported ED use (13.4%, n = 268) and 4.6% (n = 91) reported AED use in the past 3 months. Majority of ED and AED users consumed these beverages monthly or less. ED and AED users are more likely to be aged 18 to 24 years, live in a metropolitan area, and be moderate risk or problem gamblers. AED consumers are more likely to report moderate levels of psychological distress. Conclusions Our findings in relation to problem gambling and psychological distress are novel and require further targeted investigation. Health promotion strategies directed toward reducing ED and AED use should focus on young people living in metropolitan areas and potentially be disseminated through locations where gambling takes place.